Xenoantiserum to human C3 receptors: its preparation and effect on the C3b and C3d receptors of tonsil cells and the C3b receptors of erythrocytes and neutrophils. - Gerdes, J (1980)
Antisera directed against complement (C3) receptors on human tonsil cells were prepared and tested for their capacity to block specifically C3 receptors on various types of human cells. The antisera were capable of blocking both membrane-bound and solubilized C3 receptors of human tonsil cells. The C3b receptors of human erythrocytes and granulocytes were also blocked by the anti-C3 receptor sera. Sheep erythrocyte rosette formation was not affected. IgG-EoxA rosette formation was only slightly reduced by the anti-C3 receptor sera. Immunofluorescent staining with anti-C3 receptor sera revealed only a faint or negative staining of T cells and a distinct staining of EAC-reactive tonsil cells, lymphocytic leukaemia cells, and granulocytes. Absorption of the antisera with human serum proteins, brain, thymus, liver, EU-1 cell line cells, or trypsinized tonsil cells did not influence the capacity of the anti-C3 receptor sera to inhibit C3 receptors, whereas absorption with splenic tissue or tonsil cells completely removed the blocking activity of the anti-C3 receptor sera. Absorption with human erythrocytes or kidney removed only the inhibitory effect of the antisera on C3b receptors of tonsil cells, human erythrocytes, and granulocytes, but not on C3d receptors of tonsil cells. The results indicate that (a) the antisera prepared with the described procedure contained significant amounts of antibody against C3 receptors, (b) the receptors for C3b and C3d differe in antigenicity, and (c) the C3b receptors of tonsil cells, human erythrocytes, granulocytes, and probably glomerular cells have common antigenic sites.